Synthesis and characterization of novel zwitterionic poly(aryl ether oxadiazole) for antifouling ultrafiltration membrane. Issue 5 (October 2021) - Wang, Zhaofeng; Sun, Nan; Ma, Xi; Gu, Jiyou; Huo, Pengfei; Liu, Yang; Liu, Changwei
Abstract: Zwitterionic polymers have attracted widespread attention and are recognized as ideal materials in various potential applications of membrane-based separation due to its superior hydrophilicity and excellent antifouling properties. Therefore, a new type of bisphenol monomer with two tertiary amine groups named 2, 2'-dimethylaminemethylene-4, 4'-dihydroxydiphenylmethane (DABPM) was particularly designed and prepared. Then, the novel poly(aryl ether oxadiazole) (ZPAEO) was synthesized by low-temperature polycondensation and quaternary amination reaction. The chemical structures of the synthetic monomer and polymers were characterized by MS NMR and XPS analysis, and the inherent viscosities, molecular weights and solubility behaviors of the obtained polymers were also thoroughly studied. Subsequently, the ZPAEO membrane was fabricated by through the immersion precipitation phase inversion method. Compared with the reference PAEO membrane, the pore size, porosity and hydrophilicity of the ZPAEO membrane were greatly improved because of the existence of zwitterionic groups, resulting in a significant increase in the water permeability. The results of static adsorption and dynamic cycle ultrafiltration experiments of bovine serum albumin (BSA) solution showed that the ZPAEO membrane had excellent antifouling performance, which was demonstrated by the flux decline ratio. In addition, water flux recovery ratio of the ZPAEO membrane was retained at 97.7% after a three-cycles of BSA solution filtration, which was much higher than that of the PAEO membrane (81.2%), indicating superior long-term performance stability. As a membrane material, ZPAEO is expected to be widely used in various industrial separation and purification fields, which can be demonstrated by these findings. Graphical Abstract: ga1 Highlights: ZPAEO was synthesized from a new bisphenol monomer via polycondensation and quaternary amination reactions. ZPAEO membrane exhibited improved hydrophilicity and water permeability. ZPAEO membrane showed enhanced antifouling property and long-term performance stability. This approach is facile and scalable for the large-scale preparation of antifouling membranes.